ANALISIS POTENSI PELANGGARAN ETIKA DAN HUKUM DALAM PRAKTIK PODCAST JURNALISTIK DI INDONESIA - Muhammad Alberto Persada (Journal of Indonesian Comparative of Syari'ah Law, 2025)
Advances in digital technology have given rise to a new form of innovation in the world of journalism, namely journalistic podcasts. However, the emergence of this format also has the potential to give rise to various ethical and legal violations in its implementation. The purpose of this study is to analyze and provide input for journalistic podcast practitioners to avoid potential ethical and legal violations. The research method used is a normative research method. The research findings indicate that journalistic podcast practitioners have the potential to commit ethical violations, including failing to verify and confirm information sources, failing to adhere to the principle of balance, failing to respect the privacy of others and the identity of children, failing to immediately retract and correct erroneous and inaccurate podcast content with an apology, and failing to provide the right of reply and correction proportionally. Potential legal violations by journalistic podcast practitioners include defamation and slander, the spread of false or fabricated news, violations of personal data, hate speech, and copyright infringement.